Efeito do exsudado da raiz de hortelã vergamota (Mentha X piperita var citrata) sobre monogenoides em tilápias do Nilo (Oreochromis niloticus) criadas em sistema de aquaponia - Silva, Thiago Andrade da (2020)
Plants release, by theirs roots, organics compounds with diferentes properties and activities. It have known that Mentha piperita has residues released through its root system with allelopathic effect. Also it is known the antiparasitic effect of pepper mint in fish monogeneans. Aquaponics systems uses the same water and determined structures to raise fishes and vegetables simultaneously. Then, the objective of this study is research whether bergamot mint (Mentha X piperita var citrata) controls a monogeneans infestation in Nile tilapia (Oreochromis niloticus) by theirs roots exuded, in aquaponics system. Two trials were done. The first one was done in two treatments with four repetitions, with 30 Nile tilápias each. It was used juveniles whose mean weight was 7.7 g. The trial was 60 days long. The treatments was: without mint and with mint associated, in low quality water. It was observed increase of 13.3% in the survival rate (although with parasites), as well biomass (11.3%), in which had mint, suggesting that plant contributed for animals sanity and performance, but without antiparasitic effect. The second trial used three treatments with four repetitions each one, during 45 days. The treatments were: aquaponics with lettuce (Lactuva sativa; CA), aquaponics with bergamot mint (CH) and fish culture without vegetables (SP), in water with adequate quality for Nile tilapia. It were utilized 22 Nile tilápia juveniles, with 1.9 g ± 0,45 mean weigh. In the treatments with plants associated, there were a significant increase in mean weigh (3.89 g ± 0.18 – CA; 4.15 g ± 0.17 – CH; e 3.49 g ± 0.18 – SP; p<0.05), as well water quality maintenance for ammonia (0.44 – CA; 0.38; e 1.25 – SP; p<0.05) and pH (6.86 – CA; 6.80 – CH; e 5.64 – SP; p<0.05), regardless of vegetable specie. Parasitological indices did not differ statistically between the treatments. So, can be concluded that plants, as fishfarm system factor, contribute in effect way, for the animals performance, specially, by the quality water control. However, it did not possible conclude that exude of bergamot mint roots can controls monogeneans population in Niletilpia.